Covid-19 in Malaysia : Number at glance as of 14th August 2020, 12 pm - Malaysia, Kementerian Kesihatan (Kementerian Kesihatan Malaysia (KKM), 2020)
This item is made available on Ministry of Health Malaysia, Covid-19 homepage at http://covid-19.moh.gov.my/